2015
DOI: 10.1016/j.ygeno.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of gene-expression changes in an induced mouse model of spinal muscular atrophy by an antisense oligonucleotide that promotes inclusion of SMN2 exon 7

Abstract: Spinal muscular atrophy (SMA) is a neuromuscular disease caused by disruption of the survival motor neuron 1 (SMN1) gene, partly compensated for by the paralogous gene SMN2. Exon 7 inclusion is critical for full-length SMN protein production and occurs at a much lower frequency for SMN2 than for SMN1. Antisense oligonucleotide (ASO)-mediated blockade of an intron 7 splicing silencer was previously shown to promote inclusion of SMN2 exon 7 in SMA mouse models and mediate phenotypic rescue. However, downstream m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
6
27
0
Order By: Relevance
“…Several previous studies, including ours, have reported strong up-regulation of Cdkn1a/p21, a cyclin-dependent kinase inhibitor and mediator of cell cycle arrest downstream of p53, as well as other regulators of cell cycle and DNA repair in SMA models (6,19,(23)(24)(25). Whereas the Cdkn1a up-regulation has been attributed to a p53-independent stabilization of Cdkn1a transcript in the absence of SMN protein (26,27), few other gene expression changes can be explained by such posttranscriptional regulation.…”
Section: Significancementioning
confidence: 52%
See 4 more Smart Citations
“…Several previous studies, including ours, have reported strong up-regulation of Cdkn1a/p21, a cyclin-dependent kinase inhibitor and mediator of cell cycle arrest downstream of p53, as well as other regulators of cell cycle and DNA repair in SMA models (6,19,(23)(24)(25). Whereas the Cdkn1a up-regulation has been attributed to a p53-independent stabilization of Cdkn1a transcript in the absence of SMN protein (26,27), few other gene expression changes can be explained by such posttranscriptional regulation.…”
Section: Significancementioning
confidence: 52%
“…We also performed a parallel induction experiment to understand the time course of splicing and gene expression changes using 15-wkold mice that were injected with the control or skip oligo and aged for 10, 20, or 30 d. Spinal cords were then harvested and processed for RNA analysis as described previously (6). As expected, the levels of intron retention increased between 10 d and 30 d postinduction ( Fig.…”
Section: Smnmentioning
confidence: 78%
See 3 more Smart Citations